Three-dimensional reconstruction and design of patient-specific implant using open-source software - Abdullah, Johari (2019)
The commercial medical imaging software is typically expensive. Moreover, studies on three-dimensional (3D) skull reconstruction and design of patient-specific implant using free open-source software are scanty. This study aimed to compare the 3D skull models and patient-specific implants reconstructed from computed tomography (CT) images using the open-source software with commercial software. In the first stage of the study, the commercial Mimics v17.0 software was used to reconstruct the 3D skull models from 58 subjects who underwent CT scan at Hospital USM. Next, three open-source software, MITK Workbench 2016.11, 3D Slicer 4.8.1, and InVesalius 3.1, were used to reconstruct the 3D skull models from the same subjects. The 3D skull models from the commercial and open-source software were exported in standard tessellation language (STL) format into 3-matic v9.0 and CloudCompare software for analyses. SPSS version 24.0 was used for statistical analyses. For the first stage of the study, one-way ANOVA demonstrated that no significant difference was found on the craniometric analyses performed on 3D skull models reconstructed using the commercial software and the three open-source software, p > .05. Hausdorff distance (HD) analysis demonstrated the average points distance of Mimics versus MITK was 0.25 mm. Meanwhile, for Mimics versus 3D Slicer and Mimics versus InVesalius, there were almost no differences between the two superimposed 3D skull models with average points distance of 0.01 mm. Based on Dice similarity coefficient (DSC) analysis, the similarity between Mimics and MITK, Mimics and 3D Slicer, and Mimics and InVesalius were 94.1%, 98.8%, and 98.3%, respectively. In the second stage of the study, patient-specific implants were designed using the commercial 3-matic v9.0 software and open-source MITK Workbench 2016.11 software for ten decompressive craniectomy patients. The shape-based interpolation method was used, in which the technique of segmenting every fifth and tenth slices of CT data were performed. The final design of patient-specific implants from both software was exported to STL format into CloudCompare software for analyses. Results of Kruskal-Wallis test for the surface and volume of patient-specific implants designed using 3-matic and the two MITK techniques showed no significant difference, p > .05. Results of HD analysis for patient-specific implants designed using 3-matic software and the two different MITK techniques showed the average points distance for 3-matic versus MITK on every tenth slice was 0.28 mm and for 3-matic versus MITK on every fifth slice was 0.15 mm. Results of DSC analysis for patient-specific implants designed using 3-matic and the two different MITK techniques showed the similarity between 3-matic and MITK on every tenth and fifth slices were 85.1% and 89.7%, respectively. In conclusion, the open-source software investigated in this study are comparable with the commercial software for 3D reconstruction of CT images as well as designing the patient-specific implants. This is the first study on designing patient-specific implant based on CT images applying shape-based interpolation method using the free open-source software.